Professional Competence Development of Teaching Staff in Higher Education Institutions under Martial Law - Mark Vaintraub (Educational Challenges, 2024)
The purpose of this article is to show the problems of professional competence development of higher-education teaching staff under martial law. The relevance and necessity of developing teachers’ professional competence focused on specific requirements and challenges, in particular in the conditions of martial law, is emphasized.